IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING RECOUNT TEXT THROUGH PEER RESPONSE TECHNIQUE - Adinda Zoraya Alvin and Masitowarni Siregar (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2013)
This study concerned with the improvement of students’ achievement in writing recounttext by applying Peer Response technique. The objective of this study was to discoverwhether peer response technique could significantly improve students’ achievement inwriting recount text. It was conducted by using classroom action research which wascarried out in two cycles in six meetings. The subject of the research was class X-1SMA Negeri 1 Deli Tua. The number of the students was 32. The instruments forcollecting data were writing tests as the quantitative data and diary notes, observationsheet, interview sheet and questionnaire sheet as qualitative data. Based on the students’writing test, the students’ score was improved in every test. In the first test, the meanscore was 62.93. In the second test, the mean score was 72.21. In the last test, the meanscore of the students was 77.28. In line with the data, it was showed that peer responsetechnique significantly improved student’s achievement in writing recount text.